The Expert Patient and Chronic Respiratory Diseases - Louis-Philippe Boulet (Canadian Respiratory Journal)
The concept of “expert patient” has been developed in the last two decades to define a patient who has a significant knowledge of his/her disease and treatment in addition to self-management skills. However, this concept has evolved over the last years, and these patients are now considered, not only to be more efficient in the management of their own condition and communicating effectively with health professionals, but to also act as educators for other patients and as resources for the last, provide feedback on care delivery, and be involved in the production and implementation of practice guidelines, as well as in the development and conduct of research initiatives. There are some barriers, however, to the integration of this new contributor to the health care team, and specific requirements need to be considered for an individual to be considered as an expert. This new player has, however, a potentially important role to improve current care, particularly in respiratory health.